Spontaneous formation of single component liposomes from a solution. (June 2017) - Phapal, Sopan M.; Has, Chandra; Sunthar, P.
Graphical abstract: Highlights: Unilamellar liposomes formed on stationary contact of two miscible phases. The diameter is intrinsic and the first experimental evidence of spontaneous formation for a single component lipid. The diameter agrees with estimates from Helfrich's theory. Temperature and acyl chain (length and unsaturation) affect the size. Abstract: The diameter of lipid vesicles is generally known to be determined by parameters external to the system, such as fluid shear, electric fields, co-surfactants, etc. We present a mechanism by which a system consisting of a single component lipid can spontaneously assemble from a solution phase to form monodisperse unilamellar vesicles of well-defined diameters dictated only by thermodynamic parameters intrinsic to the system. Here, the lipids self-assemble as vesicles when an aqueous phase diffusively replaces the original solvent in a macroscopically stationary (or quiescent) manner. We demonstrate this using phosphatidyl choline lipid–ethanol–water systems, where the average diameter of the liposomes is shown to be intrinsic, in reasonable agreement with the Helfrich's model of the vesicle free energy. The size depends only on the temperature and the lipid type, eliminating dependence on kinetic effects or external forcing normally observed. The method provides the first pure system to study the self-assembly of vesicle-forming surfactants; and with a natural thermodynamic length scale, it may have an implication for the vesicle size selection under pre-biotic conditions.